Responses of broilers to triiodothyronine hormone and iodine supplements in cold environment - Seven, P. Tatli; Yilmaz, S.; Seven, I.; Dalkilic, B. (My University, 2009)
In this study, 150, one-day-old, broiler chicks (Ross 308) were used. The experimental groups were as follow: group I(control) was fed basal diet, group II was fed with basal diet supplemented with 1 mg/ kg T3, group III was fed with basal diet supplemented with 1.5mg/kg T3, group IV was fed with basal diet supplemented with 2 mg/kg iodine as calcium iodate, group V was fed with basal diet supplemented 3 mg/ kg iodine. Plasma T3 hormon levels of control groups were higher than that of experimental groups. It was found statistically a significant increase in malondialdehyde (MDA) levels in plasma, liver and heart in control group. The catalase.